SURVEI MANAJEMEN WAHANA OUTBOUND DI PANCASAN DREAM LAND PARK KABUPATEN BANYUMAS TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this research is to know the management consists of planning, organizing, directing and monitoring the outbound in the Pancasan Dream Land Park Regency of Banyumas by 2013.Research methods used include observation, interviewing, documentation,. The target of this research is the General Manager, coordinating financial and equipment as well as visitors.Results of the study 1) planning process conducted by the management Pancasan Dream Land Park has been running in accordance with the functions of management organization Management 2) already implement the basics of a good organization. 3) Process a briefing conducted by a General Manager 4) Supervision carried out by the management Pancasan Dream Land Park has been running according to their functions.The conclusion that the process of planning, organizing, directing, and supervising the management of the outbound in the Pancasan Dream Land Park Regency of Banyumas by 2013, and have executed management functions and processes, as appropriate.